Epistemological concepts and teaching practice of Mexican high school (bachillerato) history teachers: a narrative study - Castillo Villapudua, Karla (2021)
In this article, interviews with six history teachers at the upper secondary level are analyzed in order to review and reflect on their epistemological conceptions. The method used was qualitative and narrative research was used; using the in-depth interview technique. Among the main findings, it is worth noting that most teachers have a misconception of the concept of History, of the use of sources, of historical time, as well as of its epistemology. Likewise, some teachers do not have the appropriate professional profile to teach the discipline, so, in summary, their critical reflection is precarious when faced with questions about the meaning of history, which influences the reorientation of the teaching of discipline.